DETERMINANTS OF TECHNOLOGY ADOPTION IN CULTIVATION OF WINTER RICE IN ASSAM: AN ORDERED LOGIT ANALYSIS - Utpal Kumar DE; Ratna Kumari TAMANG (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The largest agrarian state in India’s North-East, Assam exhibited varied growth of agrarian technology at regional level since 1950. The growth of modern technology in agriculture is expected to work as impetus to agricultural productivity and farmers’ welfare. Adoption of technology such as improved seed variety and use of machine has resulted in increase in yield of winter rice. Striking difference in yield could be observed between adopters and non-adopters of technology. Ordered Logit model is applied to estimate the impacts of different factors on the adoption of agricultural technology. The result reveals that cultivated area, yield and the experience of farmers have significant positive impacts on the adoption of modern technology for the cultivation of winter rice. The findings are in support of building agrarian infrastructure and facilitation for adoption and suitable technological transformation for the enhancement of yield and sustainable agricultural progress.